Factors Influencing Individuals’ Voluntary Adoption of Mobile Commerce Services Among Malaysians - Suncheleeva, Yuliya (2013)
With the rapid spread of mobile devices, such as mobile phones,PDAs,and tablet computers,mobile commerce is widely considered to be a driving force for next generation e-commerce.Telecom companies are offering new opportunities to users over mobile devices like cellular phones and personal digital assistants. Reading-emails, surfing the WEB and sending SMS messages between cellular phones are becoming natural in our daily lives. M-commerce is an extension of e-commerce,whereby the transactions of businesses are conducted in a mobile environment using mobile devices. Explosive growth of mobile phones usage and technology innovations, such as faster data transmission, enhanced data storage, improved computing capacity and better user interface are the major driving forces behind the success of m-commerce. M-commerce has much potential in developing countries as small and medium sized companies in remote areas can use it to reach many potential customers. Despite the high rate of mobile device usage in Malaysia, m-commerce adoption remains relatively low. The adoption of technologies such as 3G,4G,WiMax also rather low in Malaysia when paralleled to developed countries. In the next few years Malaysian businesses and government have to make significant efforts to catch up with the leading countries in mobile commerce development. The main objective of this study is to investigate the factors influencing adoption of m-commerce activities in Malaysia. This study would attempt to fill the existing research gap by developing a model that predicts a consumers’ decision to adopt m-commerce. The results from this study will be useful for businesses and government in formulating their marketing strategies for mobile commerce.